Teacher's educational capacity and achievement of competences during its clinical practices in the nursing internal of the Emergency Hospital Grau Essalud, 2019. - García Caldas, Diana Alicia (2021)
Objective: To identify the relationship between the teaching capacity of the teacher tutor and the achievement of competencies of the Nursing intern during their clinical practices at the Grau Emergency Hospital in 2019. Methods. Study with a quantitative approach, relational level and non-experimental design. Through non-probabilistic convenience sampling, a sample of 50 nursing interns from the Grau EsSalud emergency hospital was used. Results. Most were between 20 and 27 years old (56%), and female (98%). The teaching capacity of the teacher achieved a regular (62%) and good (34%) level, and the achievement of the nursing interns' competencies was at a level achieved in 46%. There was a considerable direct relationship between the teaching capacity of the teacher and the achievement of competencies of the nursing intern during their clinical practices, (rho=0.793; p=0.000), as well as a direct and considerable relationship between the achievement of competencies of the nursing intern and the didactic capacity of the teacher in its communication dimensions (rho=0.785; p=0.000), and didactics (rho=0.806; p=0.000). Conclusion. There is a considerable direct relationship between the teaching capacity of the teacher and the achievement of competencies during their clinical practices in the Nursing internship of the Hospital de Emergencias Grau EsSalud, 2019.